2019
DOI: 10.1039/c9cc04141a
|View full text |Cite|
|
Sign up to set email alerts
|

4′-Guanidinium-modified siRNA: a molecular tool to control RNAi activity through RISC priming and selective antisense strand loading

Abstract: We present synthesis, biochemical, biophysical and computational evaluation of 4′ gunanidino modified siRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The incorporation of 8 nucleosides into an siRNA passenger strand showed RNAi activity identical to the unmodified siRNA, with 50% of the siRNA strands remaining intact after 48 h in 20% BSA [ 214 ]. Recent work on the synthesis of novel 4'- C -guanidinocarbohydrazidomethyl-5-methyluridine (GMU) ( Figure 9K ) has shown that functionalizing the C4' position with guanidinium leads to siRNAs with increased thermal stability (1–3 °C/mod) and improved stability in human serum [ 215 ]. These guanidinium-modified siRNAs also lead to sustained gene silencing with only picomolar concentrations after 96 h of transfection [ 215 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of 8 nucleosides into an siRNA passenger strand showed RNAi activity identical to the unmodified siRNA, with 50% of the siRNA strands remaining intact after 48 h in 20% BSA [ 214 ]. Recent work on the synthesis of novel 4'- C -guanidinocarbohydrazidomethyl-5-methyluridine (GMU) ( Figure 9K ) has shown that functionalizing the C4' position with guanidinium leads to siRNAs with increased thermal stability (1–3 °C/mod) and improved stability in human serum [ 215 ]. These guanidinium-modified siRNAs also lead to sustained gene silencing with only picomolar concentrations after 96 h of transfection [ 215 ].…”
Section: Reviewmentioning
confidence: 99%
“…Recent work on the synthesis of novel 4'- C -guanidinocarbohydrazidomethyl-5-methyluridine (GMU) ( Figure 9K ) has shown that functionalizing the C4' position with guanidinium leads to siRNAs with increased thermal stability (1–3 °C/mod) and improved stability in human serum [ 215 ]. These guanidinium-modified siRNAs also lead to sustained gene silencing with only picomolar concentrations after 96 h of transfection [ 215 ]. Their qPCR experiments show that the cause of this sustained gene silencing activity is due to enhanced guide strand recruitment within the RISC complex [ 215 ].…”
Section: Reviewmentioning
confidence: 99%
“…The effect of 4′‐ C ‐aminomethyl‐2′‐ O ‐ethyl (4′‐AM‐2′‐OEt) and 4′‐ C ‐azidomethyl‐2′‐ O ‐ethyl‐uridine (4′‐AzM‐2′‐OEt) chemical modifications on RNA duplex were studied using molecular dynamics (MD) simulations. Comparisons of MD results for these modifications executed using results from the MD simulations of 2′‐OH‐uridine unmodified and 2′‐ O ‐ethyl‐uridine (2′‐OEt) modified RNAs [33,49,50] (Figure 4). The C2′‐ endo conformers of 4′‐AM‐2′‐OEt and of 4′‐AzM‐2′‐OEt as seen in the stereoelectronic study was used to calculate the RESP charges using the RED tools package.…”
Section: Resultsmentioning
confidence: 99%
“…We also report a new route for synthesizing 2′‐ O ‐ethyl‐uridine nucleoside C (2′‐OEt−U) in just 3 steps (Figure 1). The synthesis of 2′‐ O ‐methyl and 2′‐ O ‐ethyl uridine ribonucleoside phosphoramidites and their incorporation into oligoribonucleotides were reported previously in the literature [31–33] . To the best of our knowledge, the influence of 2′‐ O ‐ethyl modification on sugar conformation has not been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar 2¢-modifications include 2¢-O-Me, 2¢-F, 2¢-MOE, locked nucleic acids (LNA), 2¢-O-allyl, 2¢-O-aminoethyl, 2¢-Oguanidinoethyl, and 2¢-O-cyanoethyl, of which 2¢-O-Me and 2¢-F are extensively studied at clinical trials and already being used in recently approved drugs, Patisiran and Givlaari [15][16][17]. Likewise, various 2¢,4¢-dual modifications have also been explored in ribose, including 4¢-AM-2¢-O-Me, 4¢-AMEt-2¢-O-Me, 4¢-AMPr-2¢-O-Me, 4¢-AMEt-2¢-F, 4¢-O-Me-2¢-F, 4¢-F-2¢-O-Me, and 2¢,4¢-di-O-Me [41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%